Nucleation and Condensation of Magnesium Vapor in Argon Carrier - Jibiao Han (Metals, 2020)
The nucleation and condensation of Magnesium (Mg) vapor carried by argon gas (Ar) were examined. The condensation of Mg vapor at a heat source temperature of 1273–1473 K and Ar flow rate of 0.1–0.4 m3/h was analyzed. The result indicated that the condensation temperature is affected by the heat source temperature and Ar flow rate, and the condensation temperature of Mg vapor was 1013.3 K at a heat source temperature of 1473 K and Ar flow rate of 0.2 m3/h. The effects of Mg vapor partial pressure and temperature of the condensation zone on the nucleation and condensation of Mg vapor carried by Ar were calculated and analyzed in terms of atomic collisions and critical nucleation radius. Increased vapor oversaturation and decreased condensation temperature were favorable for liquid nucleation growth. The Mg condensation products in Ar flow rate of 0.2 m3/h at a heat source temperature of 1473 K were analyzed by XRD, SEM, and EDS, which indicated that the condensed product was of high purity and not easily oxidized in Ar flow. In this paper, the quality of Mg vapor condensation was controlled, which provided the theoretical and experimental basis for a continuous Mg production process.